Parameter analysis and performance optimization for the vertical pipe intake-outlet of a pumped hydro energy storage station. (December 2020) - Zhang, Han; Gao, Xueping; Sun, Bowen; Qin, Zixue; Zhu, Hongtao
Abstract: The vertical pipe intake-outlet plays an important role in the pumped hydro energy storage (PHES), and its main parameters included the orifice height ratio ( H ∗), the diffuser short semi-axis ratio ( a ∗), the diffuser long semi-axis ratio ( b ∗) and the cover plate radius ratio ( R c ∗). The aim of this study was to analyse effects of the parameters and obtain the optimal design. An integration method combining computational fluid dynamics (CFD), response surface methodology (RSM) and genetic algorithm was proposed. To evaluate grid independency, the grid converge index was introduced. Based on the validation for the baseline design ( H ∗ = 0.577, a ∗ = 1.087, b ∗ = 4.231 and R c ∗ = 1.635), a reliable CFD model was developed to obtain results of sample points. Then RSM models were constructed and assessed, and contribution and interactions of the parameters were analyzed. Finally, the optimal design ( H ∗ = 0.422, a ∗ = 1.177, b ∗ = 5.363 and R c ∗ = 2.115) was obtained. The CFD results show that the overall head loss coefficient, the inflow and the outflow velocity distribution coefficient are reduced by 4.687%, 11.765% and 38.596%, respectively. Especially, the negative velocity at the trashrack section in the pump mode is eliminated. The improvement demonstrates that the proposed method achieves significant superiority over the trial-and-error method traditionally adopted in the intake-outlet design. Highlights: A vertical pipe intake-outlet was improved using an integrated optimization method. GCI was introduced into the integrated method to evaluate the influence of grid levels. RSM were constructed based on the analysis of variance and the check of residual plots. Individual effects and interactions of the parameters were analyzed. The optimal solution was validated and compared with the baseline.